ASSESSMENT OF LIFESTYLE PRACTICES, MEDICATION ADHERENCE AND CARDIOVASCULAR COMPLICATIONS OF METABOLIC SYNDROME IN GERIATRIC INPATIENTS AT TERTIARY CARE HOSPITAL - Vishwas A T L, Ritesh Agrawal (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Background: Metabolic syndrome is the major risk factor for cardiovascular diseases. The combination of proper education, good lifestyle practices, and medication adherence helps to improve good therapeutic effect and quality of life. And also, prevent cardiovascular complications. Objective: To assess the lifestyle practices and cardiovascular complications of metabolic syndrome in geriatric patients. And also, to evaluate the medication adherence and barriers for non-compliance. Methodology: This was a hospital based cross-sectional study conducted for a duration of one year. Totally, 650 of both male and female patients of age above 65 were enrolled. Ethical approval was obtained from MIMS, Mandya. The patients who are having at least three components from the diagnostic criteria of South Asians were included. Details such as demographics, lifestyle practices, occupation, physical activity, medication adherence, and cardiovascular complications were collected and subjected to statistical analysis. Results: Among 650 patients, 344 (53%) male patients are more admitted to the hospital. There is a relationship between age, education, economic status, and area of residence with respect to metabolic syndrome. The good lifestyle practices, such as a protein and fat diet, are seen in 165 (25.6%) patients. The maximum number of patients consume 521 (80.3%) of 3 times coffee/day as a bad habit. Physical activity was seen in 216 (33.5%) patients. Medication adherence was found to be 58.9% of patients, and forgetfulness was the main barrier to non-adherence in 34 (27%) patients. Among cardiovascular complications, the majority are suffering from coronary artery diseases 104 (35%). Conclusion: Our study concludes that male patients were more prevalent, and age, income, education, and residence also influence the development of metabolic syndrome. Lifestyle practices and medication adherence both are essential to achieving good therapeutic effect and preventing cardiovascular complications in geriatric patients.